The effect of empathy skills training on the Empathetic behaviours of Midwifery students - Mahin Tafazoli (Journal of Midwifery & Reproductive Health, 2018)
Background & aim: Empathy is an important component of establishing effective communication and achieving optimal clinical results. Establishing empathic communication with pregnant women improves satisfaction, mutual trust, participation in treatment, control over delivery process, and maternal health. Therefore, this study aimed to investigate the effect of empathy training on empathic skills of midwifery students of Mashhad University of Medical Sciences, Mashhad, Iran. Methods: This quasi-experimental study was conducted on 73 midwifery students and 438 pregnant women in 2015. The students in the intervention group participated in the empathy training program including training on self-awareness and empathy skills, which was held in two 4-hour sessions for two consecutive days. Then each student was assessed by six pregnant women in terms of empathy behaviors. Data was collected using Jefferson Scale of Patient’s Perceptions of Physician Empathy. Data analysis was performed applying Chi-square, Mann-Whitney U, Wilcoxon, and paired and independent t-tests in SPSS software, version 16. Results: The pre-intervention empathy scores were 88.8±8.9 and 90.0±10.3 in the intervention and control groups. Therefore, there was no significant difference between the groups (P=0.591).The post-intervention empathy scores were 99.4±4.3 and 95.8±7.3 in the intervention and control groups, respectively. Despite the higher score of empathy in the intervention group, no significant difference was observed between the groups (P=0.063). However, the intragroup comparison demonstrated a significant increase in the post-intervention empathy score of the intervention group (99.4±4.3) in comparison to the pre-intervention score (88.8±8.9) (P